Sôbre a determinação do nitrogênio, do fósforo e do potássio no mesmo extrato - Malavolta, E.; Arzolla, J. P.; Haag, H. P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1958)
The determination of total nitrogen, phosphorus, and potassium in plant material can be carried out in a common extract prepared with sulphuric acid and 30 per cent hydrogen peroxide. Nitrogen is estimated by direct nesslerization of a suitable aliquot (1-5 ml of the 50 ml extract made out of 250 mg of dried material); in order to avoid excessive acidity, 10 ml of Nessler's reagent should be employed. An aliquot of 1-5 ml suffices for the colorimetric determination of phosphorus by the molybdenum method; to reduce the phosphomolybdate complex 2 ml of a 2% SnC12 soln are necessary. Potassium is determined by the cobaltinitrite method after elimination of ammonium salts with the aid of aqua-regia.